Transfer of learning from a modern multidisciplinary perspective - Mestre, Jose P. (Emerald Publishing Limited : IAP, 2005)
The chapters contained in the book present a new and exciting set of conceptual tools that will not only allow us to think about transfer in more productive ways, but will also enable the development of educational and measurement tools that will greatly facilitate our ability to educate the children in our schools. This volume is eclectic in bringing together researchers from psychology and science education (especially physics)--who would not normally present their ideas under the same forum--to share their views and perspectives on transfer. What we believe has emerged is a fresh look at transfer issues from a multidisciplinary perspective.
Keywords: Transfer of training.; Learning, Psychology of.; Educational psychology.; Cognition.; Education -- Educational Psychology.; elektronické knihy; electronic books